Media Pembelajaran Berbasis Android Mata Pelajaran Desain Grafis Kelas X - Joko Kuswanto (Universitas Trunojoyo Madura, 2020)
This study aims to develop android-based learning media on the subjects of grafic design class X. The research method used is research development with stages of designing, production, evaluation, and analyzing data by percentage. Based on different stages the trial was being done to experts: media experts (78,30) , the design (78), and the matter (80). So the percentage of overall value on the validation experts have eligibility criteria good. To scale individuals (80), small group (80,05) and field test (80,5). So the total value of the average percentage on of respondents with criteria good.